2022
DOI: 10.3390/molecules27082396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regioisomerism on the Antiproliferative Activity of Hydroxystearic Acids on Human Cancer Cell Lines

Abstract: A series of regioisomers of the hydroxystearic acid (HSA) was prepared, and the effect of the position of the hydroxyl group along the chain on a panel of human cancer cell lines was investigated. Among the various regioisomers, those carrying the hydroxyl at positions 5, 7, and 9 had growth inhibitor activity against various human tumor cell lines, including CaCo-2, HT29, HeLa, MCF7, PC3, and NLF cells. 10-HSA and 11-HSA showed a very weak effect. 8-HSA did not show inhibitory activity in all cell lines. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The first step for the preparation of the Ru(II)-HSA complexes is the synthesis of racemic 7-HSA and ( R )-9-HSA, while 12-HSA ( Figure 1 ) was purchased as commercially available. 7-HSA and ( R )-9-HSA were obtained in pure form following the synthetic procedures recently reported [ 38 , 48 ]. The following step involves the reaction of the HSAs with a stoichiometric amount of [Ru(H) 2 CO(PPh 3 ) 3 ], 1 —obtained according to slightly modified reported processes [ 49 ]—and the synthesis selectively leads to the targeted Ru(II)-HSA complexes after purification as a unique species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first step for the preparation of the Ru(II)-HSA complexes is the synthesis of racemic 7-HSA and ( R )-9-HSA, while 12-HSA ( Figure 1 ) was purchased as commercially available. 7-HSA and ( R )-9-HSA were obtained in pure form following the synthetic procedures recently reported [ 38 , 48 ]. The following step involves the reaction of the HSAs with a stoichiometric amount of [Ru(H) 2 CO(PPh 3 ) 3 ], 1 —obtained according to slightly modified reported processes [ 49 ]—and the synthesis selectively leads to the targeted Ru(II)-HSA complexes after purification as a unique species.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available 12-HSA was purchased from Merk (Darmstad, Germany). 7-, 9-HSA were prepared by published methods [ 38 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modifications of the plant-derived bioactive compounds can confer them improved solubility and pharmacokinetic properties. For example, Calonghi and coworkers have recently tested a series of regioisomers of the hydroxystearic acid (HSA) on different cancer cell lines, finding that positional isomers possess distinct biological activities [ 125 ]. Although osteosarcoma cells were not included in this paper, it opens a new avenue for studying how chemical modification of known natural compounds can modulate their activity.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…At the same time, Calonghi et al synthesized derivatives of 9HSA and studied their antiproliferative activity on HT29 cancer cells [12]. Most recently, Calonghi et al studied the effect of regioisomerism on the antiproliferative activity of HSAs on human cancer cell lines and reported that 5HSA not only presented antiproliferative activity, but also induced changes in cell displacement, directionality and speed [13]. To extend our knowledge on HFA bioactivities and to complete structure-activity relationship studies, we decided to synthesize chiral HPAs and HSAs carrying a hydroxyl group at the 6-, 8-and 11-positions and (R)-and (S)-7-hydroxymargaric acids (7HMAs), as well as unsaturated 7-hydroxyoleic acid and 7-hydroxypalmitoleic acid, which have not previously been prepared and tested.…”
Section: Introductionmentioning
confidence: 99%